Implementation of Gesture Recognition Technology for Self-Education Service Platform - Makahaube, Stella; Sambul, Alwin M.; Sompie, Sherwin R.U.A. (Universitas Sam Ratulangi, 2021)
Gesture recognition technology is a technology used to identify object movements that have been recognized by machines, computers and then become commands. This study aims to be able to reduce direct physical contact, which can minimize transmission. The research with the title